2015
DOI: 10.1039/c5an00110b
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral horizontal semicircular canal occlusion induces serotonin increase in medial vestibular nuclei: a study using microdialysis in vivo coupled with HPLC–ECD

Abstract: Unilateral single semicircular canal occlusion (USSCO) is an effective treatment for some cases of intractable vertigo. All patients suffer behavioural imbalance caused by surgery, and then recover with a resumption of vestibular function. However, the compensation mechanism has not been fully evaluated. Findings suggest that serotonin (5-HT) is released from nerve terminals, and plays a vital role in the plasticity of the central nervous system. In this study, we performed surgery of unilateral single semicir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some data show that gravitational [ 34 ] and caloric vestibular stimulations [ 35 ] are followed by an increased serotoninergic neurotransmission. Other studies attest to an increase in VN serotonin concentration after unilateral labyrinthectomy [ 36 ] or unilateral horizontal semi-circular canal occlusion [ 37 ]. Consistent with these data, if TTA is thought to cause an increase in VN serotonin levels, this could explain the fact that Fluoxetine treatment disrupts the vestibular syndrome, since this treatment is supposed to raise serotonin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some data show that gravitational [ 34 ] and caloric vestibular stimulations [ 35 ] are followed by an increased serotoninergic neurotransmission. Other studies attest to an increase in VN serotonin concentration after unilateral labyrinthectomy [ 36 ] or unilateral horizontal semi-circular canal occlusion [ 37 ]. Consistent with these data, if TTA is thought to cause an increase in VN serotonin levels, this could explain the fact that Fluoxetine treatment disrupts the vestibular syndrome, since this treatment is supposed to raise serotonin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This category includes ondansetron (the most used), granisetron, tropisetron, dolasetron, and palonosetron (second generation antagonist) [ 40 ]. In an experimental model by Zhang et al, serotonin had an important role in vestibular compensation: the increase of its levels was documented after semi-circular canal occlusion [ 241 ]. Ondansetron showed a better effect in the control of nausea and vomiting, but a minor efficacy in the treatment of peripheral vertigo in comparison with promethazine [ 238 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous reports and our studies, vestibular compensation is followed with vertigo related to the long‐term change of the incoming signals from hippocampus, entorhinal cortex and vestibular cortex . In addition, medial vestibular nuclei (MVN) and primary somatosensory area are also involved in the vertigo procedure . Researchers have shown that hippocampal place cells could respond to vestibular stimulation, and vestibular stimulation could also affect neuronal cell proliferation in hippocampus .…”
Section: Figurementioning
confidence: 99%